Promotion of worker's health in brazilian qualitative approach research: a scoping review (Research, Society and Development, 2022)
This research aimed to map the main evidence of Brazilian research with a qualitative approach, in order to bring out the main perceptions and demands brought by those who are at the center of the production process: workers. This is a Scope Review carried out in the databases, LILACS, SciElo and Virtual Health Library (VHL). Of the 156 studies found, 10 composed this review, bringing as results for the discussion of this research: the meanings of work and worker autonomy, interpersonal relationships at work, the issue of gender at work, territory and access to health services and working conditions for health promotion. When dialoguing with current health promotion policies and workers' health, it was possible to highlight important gaps for the construction of a legal instrument that unifies, or proposes to cover such aspects not covered, which were discussed in this review.